The impact of information and communications technology infrastructure on economic growth: Does the financial system play an important role? - Toan Bui, Ngoc; Thi Doan, Thu-Trang (Edelweiss Applied Science and Technology, 2024)
The study analyzes the impact of information and communications technology (ICT) infrastructure on economic growth in the 10 ASEAN countries. Furthermore, the study examines the role of the financial system in this impact, which is a novelty compared to previous research. To achieve this objective, the authors utilized Bayesian methods in estimating the research model. This method shows its superiority in elucidating the impact of variables in the research model and determining the probability of these impacts occurring. The results show that ICT infrastructure positively impacts economic growth in the ASEAN countries, with a 100 percent probability of occurring. Particularly, the financial system does not only directly affect economic growth but also plays an important role in enhancing the impact of ICT infrastructure on economic growth, with a probability of 98.24%. This is an interesting finding of the study. Additionally, economic growth is significantly influenced by the control variables, which are specifically government expenditure and inflation. The findings provide a reliable foundation for the ASEAN countries to identify appropriate solutions to improve the efficiency in managing ICT infrastructure, thereby advancing economic growth.